A Human Rights Case Study on Access to Pre-exposure Prophylaxis for Female Sex Workers in South Africa - Steven Winkelman (Harvard FXB Center for Health and Human Rights, 2022)
This paper examines the extent to which access to HIV preventive medicines such as pre-exposure prophylaxis (PrEP) are ensured under the International Covenant on Economic, Social and Cultural Rights. There is a lack of human rights-focused research on access to HIV preventive medicines for vulnerable populations such as female sex workers in HIV-endemic countries. To help fill this gap, I utilized a case study approach to critically examine the rollout of PrEP for female sex workers in South Africa, drawing on the country's Bill of Rights, health care policies, and PrEP implementation. My analysis found that (1) PrEP rollout was largely physically and economically inaccessible for female sex workers outside of urban centers; (2) the dissemination of PrEP information specific to female sex workers was limited both virtually and in clinics, reducing the medicine's acceptability; and (3) South Africa's overburdened public health care system and continued criminalization of sex work limited the accessibility and quality of HIV prevention services, contributing to weak uptake of PrEP among female sex workers. To remedy these issues, state leaders should prioritize PrEP counseling and socially acceptable information dissemination; expand comprehensive, coherent, and coordinated sexual health services for female sex workers; increase the financial resources available for programs specific to female sex workers; and decriminalize sex work.